Effect of Economic Literacy and Conformity on Student Consumptive Behaviour - Nurjanah, Siti; Ilma, Risca Zaqia; Suparno, Suparno (Dinamika Pendidikan, 2018)
This study aims to determine the effect of economic literacy and conformity to consumer behavior. The research method used is a survey. The population in this study were MAN 3 Jakarta students with an affordable population of IIS and MIA 11th grade students totaling 150 students.The research aims to determine the effect of economic literacy and conformity on consumer behaviour. The research method used was a survey. The population in this study were MAN 3 Jakarta students with an affordable population of IIS and MIA 11th grade students totaling 150 students. The sampling technique was the Proportional Random Sampling with 105 respondents. The sampling technique used proportional random sampling. Based on the analysis of the requirements test, the data was normally distributed and had a linear relationship. The regression equation obtained is Ã = 23.908 - 0.430 X1 + 0.648 X2. Based on the test coefficient of determination, economic literacy and conformity have an effect on consumers by 29%. The lack of studentsâ€™ understanding of basic economic concepts such as the difficulty of students managing their finances because they prioritize their wants rather than needs. Students who often spend time with their friends and easily influenced by their friends and have low economic knowledge and understanding, will tend to be easier to have a high level of consumer behaviour. Conclusion of the research stated there was negative influence of economics literacy to the consumptive behaviour on MAN students, meanwhile the conformity has a significant positive effect on that.